Preparation method of modified activated carbon for removing formaldehyde
By acidizing pretreatment and functional modification of coconut shell charcoal, it is loaded with polyethyleneimine and manganese dioxide, and synergistically with modified hydrotalcite to form a stable composite structure, solving the problem of limited formaldehyde degradation ability in the existing technology, achieving efficient identification, adsorption and catalytic degradation of formaldehyde, and achieving continuous formaldehyde removal effect.
Patent Information
- Application Number
- CN202411871125.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-18
AI Technical Summary
In the prior art, formaldehyde degradation capacity is limited, and it is difficult to achieve continuous and efficient removal of formaldehyde.
By acidizing pretreatment and functional modification of coconut charcoal, polyethyleneimine and manganese dioxide are supported, and synergistically with modified hydrotalcite, a stable composite structure is formed to achieve selective identification, adsorption and catalytic degradation of formaldehyde.
It has achieved efficient identification, adsorption and catalytic degradation of formaldehyde, achieved continuous formaldehyde removal effect, and significantly improved the formaldehyde capture efficiency of the material.
Smart Images

Figure CN119500085A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of formaldehyde adsorption, and in particular to a method for preparing modified activated carbon for removing formaldehyde. Background Art
[0002] Formaldehyde is an extremely harmful indoor air pollutant. Long-term exposure to formaldehyde significantly increases the risk of people suffering from acute or chronic toxic diseases, and even short-term exposure may cause respiratory problems. Formaldehyde has been listed as a Class 1 human carcinogen. In some residential surveys, its average indoor concentration is often higher than the 8-hour reference exposure level recommended by the Environmental Protection Agency. About 2.8 million people worldwide are affected by indoor pollution caused by formaldehyde every year, and people spend most of their time (about 88%) indoors. Furniture and decorative coatings have a long cycle of releasing formaldehyde, which makes formaldehyde a serious threat to human health. There are currently a variety of formaldehyde adsorption materials available on the market, including activated carbon, photocatalyst materials, diatom mud, etc., which can meet the needs of different application scenarios. Physical adsorption materials are highly safe, but they also have disadvantages such as low adsorption capacity, limited environmental impact and high cost.
[0003] Coconut shell activated carbon has a developed microporous structure and a huge specific surface area, which enables it to efficiently adsorb small molecular harmful substances such as formaldehyde. Its micropore size is relatively suitable and can match well with formaldehyde molecules, thereby enhancing the adsorption effect of formaldehyde. At the same time, coconut shell itself is hard and natural and environmentally friendly. It will not cause harm to the environment and human health during production and use. The post-treatment is also relatively simple. It is a high-quality raw material for preparing activated carbon. Compared with some high-tech adsorption materials, coconut shell activated carbon has a lower cost and a higher cost-effectiveness. It can meet the demand for formaldehyde adsorption while reducing the cost of treating indoor air pollution. In order to further improve the efficiency of activated carbon in adsorbing formaldehyde, the activated carbon can be modified.
[0004] The existing patent CN201410713305.7 discloses a method for preparing activated carbon that can eliminate formaldehyde. The method uses activated carbon as an adsorption material, modifies the activated carbon by a surfactant, and then loads the modified activated carbon with a formaldehyde scavenger; and prepares activated carbon that can eliminate formaldehyde by drying the loaded activated carbon at room temperature or freeze drying. The activated carbon that eliminates formaldehyde prepared by the present invention is simple to produce and use, and has obvious effects. However, in the above technical scheme, the degradation capacity of formaldehyde is limited only by a simple combination of surfactant modification and formaldehyde scavenger loading, which makes it easy for the activated carbon to reach saturation, making it difficult to achieve continuous and efficient removal of formaldehyde. Summary of the invention
[0005] In view of this, the present invention proposes a method for preparing modified activated carbon for removing formaldehyde, so as to solve the problem in the prior art that the formaldehyde degradation capacity is limited and it is difficult to achieve continuous and efficient formaldehyde removal.
[0006] The technical solution of the present invention is achieved as follows: The present invention provides a method for preparing modified activated carbon for removing formaldehyde, comprising the following steps:
[0007] S1, acidifying and pretreating the coconut shell charcoal, dispersing the pretreated coconut shell charcoal in deionized water, adding polyethyleneimine and epichlorohydrin thereto, heating and stirring to react, and obtaining polyethyleneimine-loaded activated carbon;
[0008] S2, adding the activated carbon loaded with polyethyleneimine into a potassium permanganate solution for impregnation treatment, then dispersing the impregnated activated carbon in deionized water, adding a sodium hydroxide solution to adjust the solution pH to 7.5-8.5, adding cyclohexanol dropwise at 40-50° C., and then continuing to heat the reaction for 1-2 hours to obtain functionalized activated carbon;
[0009] S3, dispersing magnesium aluminum hydrotalcite in water, adding quaternary ammonium salt solution and sodium benzenesulfonate solution respectively, stirring and reacting at 60-70°C for 16-20h to obtain modified hydrotalcite; dispersing the modified hydrotalcite in toluene solution, adding vinyl silane coupling agent to react, and reflux reaction at 50-70°C for 7-9h to obtain vinyl hydrotalcite;
[0010] S4, then dispersing the vinyl hydrotalcite in ethanol, adding 4-amino-3-hydrazino-5-mercapto-triazole and diphenylacetone, stirring and reacting at 40-50° C. for 5-7 hours to obtain a secondary modified hydrotalcite;
[0011] S5. Disperse the secondary modified hydrotalcite and functionalized activated carbon in water, add sodium bicarbonate solution to adjust the pH to 7.5-9, add glutaraldehyde, stir and react at 40-50°C for 10-14h, and after the reaction is completed, filter, wash and dry to obtain modified activated carbon.
[0012] In the present invention, the functional modification of activated carbon is achieved by grafting polyethyleneimine and loading manganese dioxide on the surface of activated carbon, and the interlayer spacing of magnesium aluminum hydrotalcite is increased by intercalation modification, so as to improve the storage of formaldehyde; at the same time, a vinyl silane coupling agent is grafted on the surface and covalently bonded with 4-amino-3-hydrazine-5-mercapto-triazole to introduce amino groups, sulfur atoms, hydrazine groups and imidazole groups on the surface of magnesium aluminum hydrotalcite; finally, the functionalized activated carbon is covalently linked with the secondary modified hydrotalcite by glutaraldehyde to form a stable composite structure, and the selective recognition and directional enrichment of formaldehyde are achieved by modifying the amino groups, sulfur atoms, hydrazine groups and imidazole groups on the surface of the activated carbon material to provide sufficient adsorption sites and storage space for formaldehyde, and finally, the degradation and conversion of formaldehyde are promoted by the catalytic action of manganese dioxide, so as to produce a cyclic removal mode of recognition-adsorption-immobilization-catalytic oxidation, so as to achieve the effect of efficient formaldehyde removal.
[0013] On the basis of the above technical scheme, preferably, in step S1, the pretreatment includes: crushing and sieving the coconut shell charcoal to obtain granular charcoal with a mesh size of 30-60 mesh, mixing the granular charcoal with a dilute nitric acid solution, heating the reaction at 50-70°C for 4-6h, filtering, washing and drying to obtain pretreated coconut shell charcoal; the mass volume ratio of the granular charcoal to the dilute nitric acid solution is 1g:8-12ml, and the concentration of the dilute nitric acid solution is 2-5mol / L.
[0014] On the basis of the above technical scheme, preferably, in step S1, the mass ratio of pretreated coconut shell charcoal, polyethyleneimine and epichlorohydrin is 6-9:4-6:2-4, and heating and stirring are performed at 50-80°C for 6-10h.
[0015] The surface of coconut shell charcoal is activated by acidification pretreatment to increase oxygen-containing functional groups such as surface hydroxyl groups, providing active sites for subsequent modifications. At the same time, polyethyleneimine and epichlorohydrin are introduced for surface functionalization modification, in which polyethyleneimine provides a large number of amino functional groups to form a stable functionalized layer. The introduction of amino groups not only improves the adsorption of formaldehyde, but also provides reaction sites for subsequent reactions.
[0016] On the basis of the above technical scheme, preferably, in step S2, the mass ratio of the activated carbon loaded with polyethyleneimine to the potassium permanganate solution is 1:2.5-3.5, the concentration of the potassium permanganate solution is 0.005-0.02 mol / L, the immersion temperature is 30-80°C, and the immersion time is 13-16h; the mass percentage of the sodium hydroxide solution is 8-12%, and the mass ratio of the activated carbon and cyclohexanol after immersion is 1:1.5-2.
[0017] Through the impregnation treatment with potassium permanganate solution, manganese oxide active centers are formed on the surface of the activated carbon, and then manganese dioxide particles are generated on the surface of the activated carbon to achieve the adsorption and catalytic degradation of formaldehyde, converting it into harmless carbon dioxide and water, thereby achieving continuous removal of formaldehyde.
[0018] On the basis of the above technical scheme, preferably, in step S3, the mass ratio of magnesium aluminum hydrotalcite, quaternary ammonium salt and sodium benzenesulfonate is 2-3:1-2:1-2, the concentration of quaternary ammonium salt solution is 0.04-0.06 mol / L, and the concentration of sodium benzenesulfonate solution is 0.03-0.05 mol / L.
[0019] On the basis of the above technical scheme, preferably, the quaternary ammonium salt is any one of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium chloride and dodecyltrimethylammonium chloride.
[0020] On the basis of the above technical solution, preferably, in step S3, the mass ratio of the modified hydrotalcite to the vinyl silane coupling agent is 1:0.5-1.0, and the vinyl silane coupling agent is vinyl trimethoxy silane or vinyl triethoxy silane.
[0021] In step S3, the magnesium aluminum hydrotalcite is intercalated and modified by quaternary ammonium salt and sodium benzenesulfonate to increase its interlayer spacing and provide more formaldehyde storage space; then, unsaturated double bonds are introduced on the surface of the hydrotalcite by grafting with a vinyl silane coupling agent to provide reaction sites for the subsequent introduction of functional groups.
[0022] On the basis of the above technical solution, preferably, in step S4, the mass ratio of vinyl hydrotalcite, 4-amino-3-hydrazino-5-mercapto-triazole and diphenylacetone is 3-4:1-2:0.5-0.8.
[0023] In step S4, the double bonds on the vinyl hydrotalcite react with 4-amino-3-hydrazino-5-mercapto-triazole to introduce sulfur atoms, amino groups and imidazole groups on the surface of the magnesium aluminum hydrotalcite, thereby enhancing the selective recognition ability of the material for formaldehyde, achieving efficient capture of formaldehyde, preventing desorption, and improving adsorption stability.
[0024] On the basis of the above technical solution, preferably, in step S5, the mass ratio of the secondary modified hydrotalcite to the functionalized activated carbon is 1-1.5:1, and the amount of glutaraldehyde added is 5-15% of the mass of the secondary modified hydrotalcite.
[0025] The present invention provides a modified activated carbon for removing formaldehyde prepared by any of the preparation methods described above.
[0026] The preparation method of modified activated carbon for removing formaldehyde of the present invention has the following beneficial effects compared with the prior art:
[0027] (1) The modified activated carbon is prepared by sequentially loading a polyethyleneimine functional layer and manganese dioxide on the surface of activated carbon, and introducing a double-modified hydrotalcite as a synergistic carrier, and finally forming a stable composite structure through aldehyde-amine cross-linking. The modified activated carbon has excellent adsorption effect for formaldehyde adsorption, and realizes the multiple functional integration of selective recognition, efficient adsorption and catalytic degradation of formaldehyde. Among them, the polyethyleneimine layer on the surface of activated carbon and the 4-amino-3-hydrazino-5-thiol-triazole grafted on the surface of hydrotalcite introduce amino, sulfur, hydrazine and imidazole groups, which can realize the selective recognition and directional enrichment of formaldehyde. The intercalated modified hydrotalcite provides a larger interlayer space for the storage of formaldehyde molecules. Manganese dioxide as a catalytic active center can promote the oxidative degradation of formaldehyde. The functionalized activated carbon and the secondary modified magnesium-aluminum hydrotalcite work synergistically to realize the cyclic removal mode of "recognition-adsorption-immobilization-catalytic oxidation".
[0028] (2) By first covalently grafting polyethyleneimine onto the surface of activated carbon to form a stable three-dimensional network structure, on the one hand, a large number of amino active sites are provided. The amino groups can not only serve as subsequent reaction sites, but also the residual amino groups can form a stable Schiff base structure with formaldehyde molecules, thereby achieving efficient capture of formaldehyde; on the other hand, the polyethyleneimine layer can also provide a suitable microenvironment to promote the uniform nucleation of manganese dioxide on the surface of activated carbon; by loading manganese dioxide on the surface of activated carbon, manganese dioxide has a catalytic oxidation effect, which can oxidize formaldehyde, achieve complete removal of formaldehyde, and achieve the effect of continuous adsorption of formaldehyde;
[0029] (3) The intercalation modification of magnesium aluminum hydrotalcite by quaternary ammonium salt and sodium benzenesulfonate significantly increased its interlayer spacing and improved the storage space of formaldehyde molecules. Unsaturated double bonds were then introduced on the surface of hydrotalcite by vinyl silane coupling agent to provide reaction sites for subsequent functionalization. Multiple functional groups were then introduced on the surface of hydrotalcite by grafting 4-amino-3-hydrazine-5-mercapto-triazole. The amino group can react with formaldehyde to form a Schiff base to achieve chemical fixation, the hydrazine group can react with formaldehyde to form a stable hydrazone compound, and the imidazole group enhances its affinity for formaldehyde molecules through its special electronic structure. The synergistic effect of these functional groups not only provides multiple chemical adsorption sites, but also achieves selective recognition and directional enrichment of formaldehyde molecules, significantly improving the formaldehyde capture efficiency of the material. At the same time, the organic compatibility of hydrotalcite is improved by silanization modification with vinyl silane coupling agent, providing good interface bonding conditions for the composite with functionalized activated carbon. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 The present invention is a flow chart of the preparation method of modified activated carbon for removing formaldehyde. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] It should be noted that the magnesium aluminum hydrotalcite in this embodiment was purchased from Hubei Kewode Chemical Co., Ltd. with a CAS number of 11097-59-9.
[0034] Example 1
[0035] like Figure 1 As shown, this embodiment provides a method for preparing modified activated carbon for removing formaldehyde, comprising the following steps:
[0036] S1, crushing and sieving the coconut shell charcoal to obtain 50 mesh granular charcoal, mixing 10g of the granular charcoal with 100ml of dilute nitric acid solution (3.5mol / L), heating at 60°C for 5h, and after the reaction, filtering, washing and drying to obtain pretreated coconut shell charcoal;
[0037] 7.5 g of pretreated coconut shell charcoal was dispersed in 75 ml of deionized water, and then 5 g of polyethyleneimine and 3 g of epichlorohydrin were added thereto, and the mixture was heated and stirred at 65°C for 8 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain polyethyleneimine-loaded activated carbon;
[0038] S2. Add 10g of activated carbon loaded with polyethyleneimine into 30g of potassium permanganate solution (0.01mol / L), and soak at 55°C for 14.5h; then take 10g of the activated carbon after soaking and disperse it in 100ml of deionized water, add 10% sodium hydroxide solution to adjust the pH of the solution to 7.5-8.5, add 18g of cyclohexanol dropwise at 45°C, continue heating and reacting for 1.5h, filter, wash and dry while hot after the reaction is completed to obtain functionalized activated carbon;
[0039] S3, 25g of magnesium aluminum hydrotalcite was dispersed in 250ml of water, 15g of hexadecyltrimethylammonium chloride was prepared into a hexadecyltrimethylammonium chloride solution with a concentration of 0.05mol / L, 15g of sodium benzenesulfonate was prepared into a sodium benzenesulfonate solution with a concentration of 0.04mol / L, the quaternary ammonium salt solution and the sodium benzenesulfonate solution were added to the reaction solution respectively, and the mixture was stirred at 65°C for 18h. After the reaction was completed, the mixture was filtered, washed and dried to obtain a modified hydrotalcite; 10g of the modified hydrotalcite was dispersed in 150ml of toluene solution, 7.5g of vinyltrimethoxysilane was added for reaction, and the mixture was refluxed at 65°C for 8h. After the reaction was completed, the mixture was filtered, washed and dried to obtain a vinyl hydrotalcite;
[0040] S4, then disperse 35g of vinyl hydrotalcite in 350ml of ethanol, add 7.5g of 4-amino-3-hydrazino-5-mercapto-triazole and 6.5g of diphenylacetone, stir and react at 45°C for 6h, after the reaction is completed, filter, wash and dry to obtain a secondary modified hydrotalcite;
[0041] S5. Disperse 12.5 g of secondary modified hydrotalcite and 10 g of functionalized activated carbon in water, add sodium bicarbonate solution (mass percentage is 1-2%) to adjust the pH to 7.5-9, add 1.0 g of glutaraldehyde, stir and react at 45°C for 12 h. After the reaction is completed, filter, wash and dry to obtain modified activated carbon.
[0042] Example 2
[0043] This embodiment provides a method for preparing modified activated carbon for removing formaldehyde, comprising the following steps:
[0044] S1, crushing and sieving the coconut shell charcoal to obtain granular charcoal with a mesh size of 30 mesh, mixing 10g of the granular charcoal with 80ml of a dilute nitric acid solution (5mol / L), heating at 50°C for 6h, and after the reaction, filtering, washing and drying to obtain pretreated coconut shell charcoal;
[0045] 6 g of pretreated coconut shell charcoal was dispersed in 60 ml of deionized water, and then 4 g of polyethyleneimine and 2 g of epichlorohydrin were added thereto, and the mixture was heated and stirred at 50°C for 10 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain polyethyleneimine-loaded activated carbon;
[0046] S2. Add 10g of activated carbon loaded with polyethyleneimine into 25g of potassium permanganate solution (0.02mol / L), and soak at 30°C for 16h; then take 10g of the impregnated activated carbon and disperse it in 100ml of deionized water, add 8% sodium hydroxide solution to adjust the pH of the solution to 7.5-8.5, add 15g of cyclohexanol dropwise at 40°C, continue heating and reacting for 2h, filter while hot after the reaction, wash and dry to obtain functionalized activated carbon;
[0047] S3, dispersing 20g of magnesium aluminum hydrotalcite in 200ml of water, taking 10g of hexadecyltrimethylammonium chloride to prepare a hexadecyltrimethylammonium chloride solution with a concentration of 0.04mol / L, and 10g of sodium benzenesulfonate to prepare a sodium benzenesulfonate solution with a concentration of 0.03mol / L, respectively adding the quaternary ammonium salt solution and the sodium benzenesulfonate solution to the reaction solution, stirring and reacting at 60°C for 20h, after the reaction is completed, filtering, washing, and drying to obtain modified hydrotalcite; dispersing 10g of modified hydrotalcite in 150ml of toluene solution, adding 5g of vinyltrimethoxysilane to react, refluxing at 50°C for 9h, after the reaction is completed, filtering, washing, and drying to obtain vinyl hydrotalcite;
[0048] S4, then disperse 30g of vinyl hydrotalcite in 300ml of ethanol, add 5g of 4-amino-3-hydrazino-5-mercapto-triazole and 5g of diphenylacetone, stir and react at 40°C for 7h, after the reaction is completed, filter, wash and dry to obtain a secondary modified hydrotalcite;
[0049] S5. Disperse 10 g of secondary modified hydrotalcite and 10 g of functionalized activated carbon in water, add sodium bicarbonate solution (mass percentage is 1-2%) to adjust the pH to 7.5-9, add 0.5 g of glutaraldehyde, stir and react at 50°C for 10 hours. After the reaction is completed, filter, wash and dry to obtain modified activated carbon.
[0050] Example 3
[0051] This embodiment provides a method for preparing modified activated carbon for removing formaldehyde, comprising the following steps:
[0052] S1, crushing and sieving the coconut shell charcoal to obtain 60 mesh granular charcoal, mixing 10g of the granular charcoal with 120ml of dilute nitric acid solution (2mol / L), heating at 70°C for 4h, and after the reaction, filtering, washing and drying to obtain pretreated coconut shell charcoal;
[0053] 9 g of pretreated coconut shell charcoal was dispersed in 90 ml of deionized water, and then 6 g of polyethyleneimine and 4 g of epichlorohydrin were added thereto, and the mixture was heated and stirred at 80°C for 6 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain polyethyleneimine-loaded activated carbon;
[0054] S2, add 10g of activated carbon loaded with polyethyleneimine into 35g of potassium permanganate solution (0.005mol / L), and soak at 80°C for 13h; then take 10g of the impregnated activated carbon and disperse it in 100ml of deionized water, add 12% sodium hydroxide solution to adjust the solution pH to 7.5-8.5, add 20g of cyclohexanol dropwise at 50°C, continue heating and reacting for 1h, filter while hot after the reaction, wash and dry, and obtain functionalized activated carbon;
[0055] S3, 30g of magnesium aluminum hydrotalcite was dispersed in 300ml of water, 20g of hexadecyltrimethylammonium chloride was prepared into a hexadecyltrimethylammonium chloride solution with a concentration of 0.06mol / L, 20g of sodium benzenesulfonate was prepared into a sodium benzenesulfonate solution with a concentration of 0.05mol / L, the quaternary ammonium salt solution and the sodium benzenesulfonate solution were added to the reaction solution respectively, and the mixture was stirred at 70°C for 16h. After the reaction was completed, the mixture was filtered, washed and dried to obtain a modified hydrotalcite; 10g of the modified hydrotalcite was dispersed in 150ml of toluene solution, 10g of vinyltrimethoxysilane was added for reaction, and the mixture was refluxed at 70°C for 7h. After the reaction was completed, the mixture was filtered, washed and dried to obtain a vinyl hydrotalcite;
[0056] S4, then disperse 40g of vinyl hydrotalcite in 400ml of ethanol, add 10g of 4-amino-3-hydrazino-5-mercapto-triazole and 8g of diphenylacetone, stir and react at 50°C for 5h, after the reaction is completed, filter, wash and dry to obtain a secondary modified hydrotalcite;
[0057] S5. Disperse 15 g of secondary modified hydrotalcite and 10 g of functionalized activated carbon in water, add sodium bicarbonate solution (1-2% by mass) to adjust the pH to 7.5-9, add 1.5 g of glutaraldehyde, and stir the reaction at 45°C for 14 hours. After the reaction is completed, filter, wash and dry to obtain modified activated carbon.
[0058] Comparative Example 1
[0059] This comparative example provides a method for preparing modified activated carbon for removing formaldehyde, comprising the following steps:
[0060] S1, crushing and sieving the coconut shell charcoal to obtain 50 mesh granular charcoal, mixing 10g of the granular charcoal with 100ml of dilute nitric acid solution (3.5mol / L), heating at 60°C for 5h, and after the reaction, filtering, washing and drying to obtain pretreated coconut shell charcoal;
[0061] S2, add 10g of pretreated coconut shell charcoal to 30g of potassium permanganate solution (0.01mol / L), and soak at 55°C for 14.5h; then take 10g of the impregnated activated carbon and disperse it in 100ml of deionized water, add 10% sodium hydroxide solution to adjust the solution pH to 7.5-8.5, add 18g of cyclohexanol dropwise at 45°C, continue heating reaction for 1.5h, filter, wash and dry while hot after the reaction is completed to obtain functionalized activated carbon;
[0062] S3, dispersing 10g of magnesium aluminum hydrotalcite in 150ml of toluene solution, adding 7.5g of vinyl trimethoxysilane for reaction, and reflux reaction at 65°C for 8h. After the reaction, filtering, washing and drying to obtain vinyl hydrotalcite;
[0063] S4. Disperse 12.5 g of vinyl hydrotalcite and 10 g of functionalized activated carbon in water, add sodium bicarbonate solution (1-2% by mass) to adjust the pH to 7.5-9, add 1.0 g of glutaraldehyde, stir and mix at 45° C. for 12 h, filter, wash and dry to obtain modified activated carbon.
[0064] Comparative Example 2
[0065] This comparative example provides a method for preparing modified activated carbon for removing formaldehyde, comprising the following steps:
[0066] S1, crushing and sieving the coconut shell charcoal to obtain 50 mesh granular charcoal, mixing 10g of the granular charcoal with 100ml of dilute nitric acid solution (3.5mol / L), heating at 60°C for 5h, and after the reaction, filtering, washing and drying to obtain pretreated coconut shell charcoal;
[0067] S2, add 10g of pretreated coconut shell charcoal to 30g of potassium permanganate solution (0.01mol / L), and soak at 55°C for 14.5h; then take 10g of the impregnated activated carbon and disperse it in 100ml of deionized water, add 10% sodium hydroxide solution to adjust the solution pH to 7.5-8.5, add 18g of cyclohexanol dropwise at 45°C, continue heating reaction for 1.5h, filter, wash and dry while hot after the reaction is completed to obtain functionalized activated carbon;
[0068] S3-S4 are the same as in Example 1;
[0069] S5. Disperse 12.5 g of secondary modified hydrotalcite and 10 g of functionalized activated carbon in water, add sodium bicarbonate solution (1-2% by mass) to adjust the pH to 7.5-9, add 1.0 g of glutaraldehyde, stir and mix at 45° C. for 12 h, filter, wash and dry to obtain modified activated carbon.
[0070] Comparative Example 3
[0071] This comparative example provides a method for preparing modified activated carbon for removing formaldehyde, comprising the following steps:
[0072] S1-S2 are the same as in Example 1;
[0073] S3, 25g of magnesium aluminum hydrotalcite was dispersed in 250ml of water, 15g of hexadecyltrimethylammonium chloride was prepared into a hexadecyltrimethylammonium chloride solution with a concentration of 0.05mol / L, 15g of sodium benzenesulfonate was prepared into a sodium benzenesulfonate solution with a concentration of 0.04mol / L, the quaternary ammonium salt solution and the sodium benzenesulfonate solution were added to the reaction solution respectively, and the mixture was stirred at 65°C for 18h. After the reaction was completed, the mixture was filtered, washed and dried to obtain a modified hydrotalcite; 10g of the modified hydrotalcite was dispersed in 150ml of toluene solution, 7.5g of vinyltrimethoxysilane was added for reaction, and the mixture was refluxed at 65°C for 8h. After the reaction was completed, the mixture was filtered, washed and dried to obtain a vinyl hydrotalcite;
[0074] S4. Disperse 12.5 g of vinyl hydrotalcite and 10 g of functionalized activated carbon in water, add sodium bicarbonate solution (1-2% by mass) to adjust the pH to 7.5-9, add 1.0 g of glutaraldehyde, stir and mix at 45° C. for 12 h, filter, wash and dry to obtain modified activated carbon.
[0075] Comparative Example 4
[0076] This comparative example provides a method for preparing modified activated carbon for removing formaldehyde, comprising the following steps:
[0077] S1-S2 are the same as in Example 1;
[0078] S3, dispersing 10g of magnesium aluminum hydrotalcite in 150ml of toluene solution, adding 7.5g of vinyl trimethoxysilane for reaction, and reflux reaction at 65°C for 8h. After the reaction, filtering, washing and drying to obtain vinyl hydrotalcite;
[0079] S4, then disperse 35g of vinyl hydrotalcite in 350ml of ethanol, add 7.5g of 4-amino-3-hydrazino-5-mercapto-triazole and 6.5g of diphenylacetone, stir and react at 45°C for 6h, after the reaction is completed, filter, wash and dry to obtain a secondary modified hydrotalcite;
[0080] S5. Disperse 12.5 g of secondary modified hydrotalcite and 10 g of functionalized activated carbon in water, add sodium bicarbonate solution (mass percentage is 1-2%) to adjust the pH to 7.5-9, add 1.0 g of glutaraldehyde, stir and react at 45°C for 12 h. After the reaction is completed, filter, wash and dry to obtain modified activated carbon.
[0081] Performance Testing
[0082] Take 10g of the modified activated carbon prepared in the embodiment and the comparative example and put them into air purifiers respectively. The air volume of the air purifier is 10m 3 / h, placed at 1m 3 The temperature in the experimental chamber was 25±2℃ and the relative humidity was 50±5%. Formaldehyde was added dropwise in the experimental chamber and the initial formaldehyde concentration was 2.0±0.2mg / m 3 , turn on the purifier, take samples to test the formaldehyde concentration in the test chamber after 1h, 6h, 12h, 24h and 48h, and calculate the formaldehyde purification efficiency, which is (formaldehyde concentration before purification - formaldehyde concentration after purification) / formaldehyde concentration before purification; persistence: take the modified activated carbon prepared in the embodiment and the comparative example and put them into the closed sample chamber respectively, add formaldehyde to the sample chamber on time every day for 15 days, take out the modified activated carbon on the 16th day and put it into the air purifier, and then put it into the experimental chamber. The environment in the experimental chamber is as described above, take samples to test the formaldehyde concentration in the chamber after 48h, and calculate the formaldehyde purification rate. The test results are shown in Table 1.
[0083] Table 1 Formaldehyde adsorption effect
[0084]
[0085] It can be seen from Table 1 that the modified activated carbon prepared by the preparation method of the present invention has a good purification rate and purification durability for formaldehyde.
[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing modified activated carbon for removing formaldehyde, characterized in that: The following steps are involved: S1, acidifying and pretreating the coconut shell charcoal, dispersing the pretreated coconut shell charcoal in deionized water, adding polyethyleneimine and epichlorohydrin thereto, heating and stirring to react, and obtaining polyethyleneimine-loaded activated carbon; S2, adding the activated carbon loaded with polyethyleneimine into a potassium permanganate solution for impregnation treatment, then dispersing the impregnated activated carbon in deionized water, adding a sodium hydroxide solution to adjust the solution pH to 7.5-8.5, adding cyclohexanol dropwise at 40-50° C., and then continuing to heat the reaction for 1-2 hours to obtain functionalized activated carbon; S3, dispersing magnesium aluminum hydrotalcite in water, adding quaternary ammonium salt solution and sodium benzenesulfonate solution respectively, stirring and reacting at 60-70° C. for 16-20 hours to obtain modified hydrotalcite; Dispersing the modified hydrotalcite in a toluene solution, adding a vinyl silane coupling agent for reaction, and reflux reaction at 50-70° C. for 7-9 hours to obtain vinyl hydrotalcite; S4, then dispersing the vinyl hydrotalcite in ethanol, adding 4-amino-3-hydrazino-5-mercapto-triazole and diphenylacetone, stirring and reacting at 40-50° C. for 5-7 hours to obtain a secondary modified hydrotalcite; S5. Disperse the secondary modified hydrotalcite and functionalized activated carbon in water, add sodium bicarbonate solution to adjust the pH to 7.5-9, add glutaraldehyde, stir and react at 40-50°C for 10-14h, and after the reaction is completed, filter, wash and dry to obtain modified activated carbon.
2. The method for preparing a modified activated carbon for removing formaldehyde according to claim 1, characterized in that: In step S1, the pretreatment includes: crushing and sieving the coconut shell charcoal to obtain granular charcoal with a mesh size of 30-60 mesh, mixing the granular charcoal with a dilute nitric acid solution, heating the reaction at 50-70°C for 4-6 hours, filtering, washing, and drying to obtain pretreated coconut shell charcoal; the mass volume ratio of the granular charcoal to the dilute nitric acid solution is 1g:8-12ml, and the concentration of the dilute nitric acid solution is 2-5mol / L.
3. The method for preparing a modified activated carbon for removing formaldehyde according to claim 1, characterized in that: In step S1, the mass ratio of pretreated coconut shell charcoal, polyethyleneimine and epichlorohydrin is 6-9:4-6:2-4, and the mixture is heated and stirred at 50-80°C for 6-10h.
4. The method for preparing a modified activated carbon for removing formaldehyde according to claim 1, characterized in that: In step S2, the mass ratio of the activated carbon loaded with polyethyleneimine to the potassium permanganate solution is 1:2.5-3.5, the concentration of the potassium permanganate solution is 0.005-0.02 mol / L, the immersion temperature is 30-80°C, and the immersion time is 13-16h; the mass percentage of the sodium hydroxide solution is 8-12%, and the mass ratio of the activated carbon to the cyclohexanol after immersion is 1:1.5-2.
5. The method for preparing a modified activated carbon for removing formaldehyde according to claim 1, characterized in that: In step S3, the mass ratio of magnesium aluminum hydrotalcite, quaternary ammonium salt and sodium benzenesulfonate is 2-3:1-2:1-2, the concentration of quaternary ammonium salt solution is 0.04-0.06 mol / L, and the concentration of sodium benzenesulfonate solution is 0.03-0.05 mol / L.
6. The method for preparing a modified activated carbon for removing formaldehyde according to claim 1, characterized in that: The quaternary ammonium salt is any one of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium chloride and dodecyltrimethylammonium chloride.
7. The method for preparing a modified activated carbon for removing formaldehyde according to claim 1, characterized in that: In step S3, the mass ratio of the modified hydrotalcite to the vinyl silane coupling agent is 1:0.5-1.0, and the vinyl silane coupling agent is vinyl trimethoxy silane or vinyl triethoxy silane.
8. The method for preparing a modified activated carbon for removing formaldehyde according to claim 1, characterized in that: In step S4, the mass ratio of vinyl hydrotalcite, 4-amino-3-hydrazino-5-mercapto-triazole and diphenylacetone is 3-4:1-2:0.5-0.
8.
9. The method for preparing a modified activated carbon for removing formaldehyde according to claim 1, characterized in that: In step S5, the mass ratio of the secondary modified hydrotalcite to the functionalized activated carbon is 1-1.5:1, and the amount of glutaraldehyde added is 5-15% of the mass of the secondary modified hydrotalcite.
10. A modified activated carbon for removing formaldehyde prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
A method for preparing activated carbon that can eliminate formaldehyde
CN104324692B
Preparation method of active carbon capable of removing formaldehyde
CN104324692A
Preparation method of modified activated carbon for purifying formaldehyde in air
CN110711556A
Efficient biomass sewage purifying agent and preparation method thereof
CN114602435A
Carbon aerogel adsorption material and preparation method thereof
CN117718014A
Cited By
Activated carbon fiber capable of efficiently removing formaldehyde and preparation method of activated carbon fiber
CN120575362A
CoFe2O4-charcoal adsorption material as well as preparation method and application thereof
CN120733703A
Gradient aperture activated carbon for adsorbing formaldehyde-benzene series and preparation method of gradient aperture activated carbon
CN121490731A